Integrated Phytochemical Analysis Based on UPLC–MS/MS and Network Pharmacology Approaches to Explore the Effect of Odontites vulgaris Moench on Rheumatoid Arthritis - Ji, Mingyue; Wang, Congcong; Yang, Tieyi; Meng, Xiangxi; Wang, Xiaoqin; Li, Minhui (Frontiers in Pharmacology, 2021)
Odontites vulgaris Moench has the effect of clearing away heat, detoxification, dispelling wind, and clearing dampness. In this study, the potential anti-inflammatory compounds of O. vulgaris were investigated using ultra-high-performance liquid chromatography–mass spectrometry (UPLC–MS/MS) combined with the network pharmacology approach and further confirmed on an LPS-activated RAW 264.7 macrophage model. Monomer compounds were prepared from the active fraction using modern advanced separation and purification methods. UPLC–Q-Exactive HRMS was used to identify the chemical compounds in the active fractions of O. vulgaris. D-mannitol, geniposidic acid, salidroside, shanzhiside methyl ester, eleutheroside B, geniposide, 7,8-dihydroxycoumarin, gardoside methyl ester, arenarioside, vanillic acid, p-hydroxy-cinnamic acid, melampyroside, syringaresinol, tricin, and diosmetin were isolated from O. vulgaris for the first time. A compound database of O. vulgaris was established based on the existing literature to predict the mechanism of O. vulgaris in the treatment of rheumatoid arthritis. The results suggest that the PI3K-Akt pathway mediates O. vulgaris and deserves more attention in the treatment of RA. Finally, the anti-rheumatoid arthritis effects of the four target compounds were validated with the decreased levels of NO, TNF-α, IL-6 and IL-1β in RAW 264.7 macrophage cells treated with LPS. The present study explored the potential targets and signaling pathways of O. vulgaris in the treatment of RA, which may help to illustrate the mechanisms involved in the action of O. vulgaris and may provide a better understanding of the relationship between O. vulgaris and rheumatoid arthritis. This study provides novel insights into the development of new drugs and utilization of Mongolian traditional Chinese medicine resources.